Are electronic nicotine delivery systems (ENDs) helping cigarette smokers quit?—Current evidence. (8th November 2019) - Patil, Shankargouda; Arakeri, Gururaj; Patil, Shekar; Ali Baeshen, Hosam; Raj, Thirumal; Sarode, Sachin C.; Sarode, Gargi S.; Awan, Kamran H.; Gomez, Ricardo; Brennan, Peter A.
Abstract: Background: Electronic cigarettes (e‐cigarettes) and other electronic vaping devices are commonly used as a method to help tobacco smoking cessation. However, the data on their safety and efficacy are currently scarce. The aim of this review was to explore the role of e‐cigarettes in tobacco cessation among tobacco users. Types of Studies Reviewed: PubMed, EMBASE, Scopus, Web of Science, and grey literature from January 1990 were searched up to and including September 2018. Two independent reviewers performed the study selection according to eligibility criteria. Results: A total of 13 studies that met the eligibility criteria were included. The majority of studies were done in the USA, and all studies were longitudinal cohort studies. The odds of increased smoking cessation in association with e‐cigarette use ranged from onefold to sixfolds. No significant increase in smoking cessation was found among e‐cigarette users compared with non–e‐cigarette users. Pattern of e‐cigarette had positive influence on smoking cessation among users. Conclusions and Practical Implications: E‐cigarette use was not significantly associated with increased smoking cessation among cigarette smokers. We also found that pattern of e‐cigarette may have significant effect on smoking cessation capability of e‐cigarettes. Well‐designed randomized controlled clinical trials are needed to assess the clinical efficacy of e‐cigarettes in comparison with approved smoking cessation therapies.